ANALISIS PERFORMA PRODUKSI DAN KELAYAKAN FINANSIAL PETERNAKAN ITIK PETELUR YANG DIPELIHARA DENGAN SISTEM INTENSIF - ANNISA H. N.; I W. SUKANATA; B. R. T. PUTRI (Fakultas Peternakan Universitas Udayana, 2021)
This study aims to determine the management, production performance, financial feasibility, break-even point and sensitivity of business. The study began from December 2019 until January 2020 at UD. Sari Utama, located in Cepaka Village, Kediri District, Tabanan Regency. This research uses primary data. The variables observed in this study are livestock management, production performance, cost, financial feasibility, and sensitivity. The fe- asibility of laying duck business is analyzed using investment criteria analysis, PBP, BEP and sensitivity analysis. The results of this study indicate that the UD Sari Utama laying duck business has paid attention to several aspects of management including the selection of pra-layer ducks, cages, feed, labor, prevention and treatment of disease. The average egg production is 65%/day and the average number of eggs produced is consumption eggs 62,4% and 37,6% hatching eggs with a maintenance ratio of male and female ducks 1:10. The results of financial analysis show that this farm produces NPV 246.749.932, IRR 26,16%, Net B / C 2,2, PBP in 1,17 years, BEP in 5,96 years, BEP egg production 217.935 / year, BEP egg price Rp 1.649,84 / item. The results of the sensitivity analysis show that the business is sensitive to decreasing egg prices and increasing feed prices, with sensitivity values of 10,52% and 16,87%, respectively. Based on these results it can be concluded that the business of laying duck UD. Sari Utama is financially feasible.